Peningkatan Proses Pembelajaran Tematik Terpadu menggunakan Model Discovery Learning di Sekolah Dasar - Saputri, Yuditia; Miaz, Yalvema (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2022)
The purpose of this research is to describe an integrated thematic learning process improvement to the model of discovery learning in fourth grade elementary school 13 Batu Gadang Padang City. In this study applying PTK research using qualitative and quantitative approaches. Where this research was conducted on the fourth grade students of SDN 13 Batu Gadang, amounting to 29 people consisting of 16 male students and 13 female students. The results showed: a) the evaluation of the first cycle Learning Implementation Plan obtained an average of 78% (C), and in the second cycle increased to 93.75% (SB). b) Observations on the aspect of the first cycle teachers obtained an average of 79.7% (C) and in the second cycle increased to 90.6% (SB). c) Observations on aspects of the first cycle students obtained an average of 79.7% (C) and in the second cycle increased to 90.6% (SB). Thus the model of discovery learning can enhance the integrated thematic learning process in elementary school.